An interface-enhanced continuous 2D-carbon network enabling high-performance Si anodes for Li-ion batteries. Issue 43 (27th October 2022) - Peng, Jiaying; Shao, Rong; Huang, Sijie; Cao, Zhenjiang; Zhang, Tianren; Cao, Yinliang; Zhang, Shuguo; Xu, Chunchuan; Shi, Yongzheng; Niu, Jin; Wang, Feng
Abstract : A continuous interface-enhanced 2-D carbon network is introduced in the Si anode by a templating method, which enhances the Li-ion diffusion and electron transport within the Si anode and stabilizes the interface between the Si anode and electrolyte. Abstract : Silicon (Si) has been regarded as a promising anode material for next-generation Li-ion batteries by virtue of its high theoretical capacity and low working potential. Although various strategies have been proposed to solve the problems of Si anodes ( e.g., poor electrical conductivity and volume effects), there is still a lack of efficient ways to simultaneously realize the high capacity, good rate capability and stability of Si anodes. Herein, an interface-enhanced 2-D carbon network is introduced into the Si anode by a simple templating method using gelatin as a carbon precursor. Electrochemical measurement, in situ Raman spectroscopy, and theoretical simulation results suggest that the unique gelatin-derived carbon nanosheet (GCNS) structure not only promotes the Li-ion diffusion and electron transport within the Si anode, but also stabilizes the Si structure. The Si anode having the interface-enhanced GCNS network (Si@GCNS) exhibits high charge capacity (2975 mA h g −1 at 0.2 A g −1 ), good rate capability (1892 mA h g −1 at 5 A g −1 ), and long lifetime (with a capacity retention of 83.4% after 400 cycles), superior to the Si-based anodes modified by 3-D or 2-D carbons. Moreover, a pouch cell based on the Si@GCNS anode and a commercial LiFePO4 cathode shows a high energy density of ∼460 W h kg −1 and good cycling performance.